Rethinking Technology-Enhanced Physics Teacher Education: From Theory to Practice - Milner-Bolotin, Marina (Canadian journal of science, mathematics and technology education, 2016)
This article discusses how modern technology, such as electronic response systems, PeerWise system, data collection and analysis tools, computer simulations, and modeling software can be used in physics methods courses to promote teacher-candidates’ professional competencies and their positive attitudes about mathematics and science education. We show how modeling technology-enhanced deliberate pedagogical thinking in physics methods courses can improve teacher-candidates’ subject-specific pedagogical knowledge and their positive attitudes about science learning. We also discuss potential challenges that must be addressed in order to help teacher-candidates successfully implement these pedagogies during the practicum and in their early years of teaching.